Antiarrhythmic drugs in patients with early persistent atrial fibrillation and heart failure: results of the RACE 3 study. Issue 9 (26th April 2021) - Al-Jazairi, Meelad I H; Nguyen, Bao-Oanh; De With, Ruben R; Smit, Marcelle D; Weijs, Bob; Hobbelt, Anne H; Alings, Marco; Tijssen, Jan G P; Geelhoed, Bastiaan; Hillege, Hans L; Tieleman, Robert G; Van Veldhuisen, Dirk J; et al.
Abstract: Aims: Maintaining sinus rhythm in patients with persistent atrial fibrillation (AF) is challenging. We explored the efficacy of class I and III antiarrhythmic drugs (AADs) in patients with persistent AF and mild to moderate heart failure (HF). Methods and results: In the RACE 3 trial, patients with early persistent symptomatic AF and short history of mild to moderate HF with preserved or reduced left ventricular ejection fraction (LVEF) were randomized to targeted or conventional therapy. Both groups received AF and HF guideline-driven treatment. Additionally, the targeted-group received mineralocorticoid receptor antagonists, statins, angiotensin-converting enzyme inhibitors and/or receptor blockers, and cardiac rehabilitation. Class I and III AADs could be instituted in case of symptomatic recurrent AF. Eventually, pulmonary vein isolation could be performed. Primary endpoint was sinus rhythm on 7-day Holter after 1-year. Included were 245 patients, age 65 ± 9 years, 193 (79%) men, AF history was 3 (2–6) months, HF history 2 (1–4) months, 72 (29.4%) had HF with reduced LVEF. After baseline electrical cardioversion (ECV), 190 (77.6%) had AF recurrences; 108 (56.8%) received class I/III AADs; 19 (17.6%) flecainide, 36 (33.3%) sotalol, 3 (2.8%) dronedarone, 50 (46.3%) amiodarone. At 1-year 73 of 108 (68.0%) patients were in sinus rhythm, 44 (40.7%) without new AF recurrences. Maintenance of sinus rhythm was significantly better with amiodarone [ n  = 29/50 (58%)] compared with flecainide [ n  = 6/19 (32%)] and sotalol/dronedarone [ n  = 9/39 (23%)], P  = 0.0064. Adverse events occurred in 27 (25.0%) patients, were all minor and reversible. Conclusion: In stable HF patients with early persistent AF, AAD treatment was effective in nearly half of patients, with no serious adverse effects reported.